MAGALHÃES, I; MARTINS, A. R.; RESENDE, V. M. Análise de Discurso Crítica: um método de pesquisa qualitativa. Brasília: Editora da Universidade de Brasília, 2017. 260 p. - Argenta, Julia Salvador (Bakhtiniana. Revista de Estudos do Discurso, 2017)
Resenha